2012
DOI: 10.1089/neu.2010.1732
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebral Extracellular Release of Glycerol, Glutamate, and FGF2 Is Increased in Older Patients following Severe Traumatic Brain Injury

Abstract: Old age is associated with a poor recovery from traumatic brain injury (TBI). In a retrospective study we investigated if the biochemical response following TBI is age dependent. Extracellular fluids were continuously sampled by microdialysis in 69 patients admitted to our NSICU following severe TBI. The concentrations of glycerol, glutamate, lactate, pyruvate, and eight different cytokines (IL-1b, IL-6, IL-10, IL-8, MIP-1b, RANTES, FGF2, and VEGF) were determined by fluorescence multiplex bead technology. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
0
32
2
Order By: Relevance
“…Of the 19 articles included in the CMD cytokine portion of the systematic review (11–19), 15 were formal manuscript publications (1424, 2629) and 4 were meeting abstract publications (11–13, 25). There were 13 prospective studies (13–16, 1821, 25–29), with 12 prospective observational studies (13–15, 1821, 25–29) and 1 prospective randomized control trial (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 19 articles included in the CMD cytokine portion of the systematic review (11–19), 15 were formal manuscript publications (1424, 2629) and 4 were meeting abstract publications (11–13, 25). There were 13 prospective studies (13–16, 1821, 25–29), with 12 prospective observational studies (13–15, 1821, 25–29) and 1 prospective randomized control trial (16).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were retrospective case series or database reviews (11, 20, 22, 23). Finally, two studies were of “unknown” study design given a lack of information available within the methods (12, 24). …”
Section: Resultsmentioning
confidence: 99%
“…The brain concentration of FGF2 is reported to be around 30 to 120 ng/mg [46]; however, some reports show that the concentration is around 50 pg/ml [47,48]. In a future study, we will attempt to clarify the effect of 100 ng/ml FGF2 in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In a study that used cerebral microdialysis in pigs undergoing TBI and HS, we found that treatment with FFP + VPA infusion led to a decrease in cerebral lactate and pyruvate compared with the FFP alone group, implying superior glucose utilization for ATP production. We also noted a decrease in concentrations of glutamate in the brains of the FFP+ VPA animals, a known excitotoxic neurotransmitter implicated as the final common pathway in neuronal injury and death (86), and glycerol, a well-established marker of membrane-phospholipid damage after TBI (87, 88). These findings suggest an overall decrease in excitotoxicity and brain damage.…”
Section: Mechanisms Underlying Vpa-induced Neuroprotectionmentioning
confidence: 84%